Using MSDI and M3Y Core Polarization for the Coulomb Electron Scattering for some Ground state nuclei - Dlshad, Hawar Muhamad; Fatah, Aziz Hama Raheem (Sulaimani Journal for Pure and Applied Sciences, 2019)
The analysis of Coulomb electron scattering for the ground state-nuclei Li6 , C12 , O18 , F19 and Ne 20 are performed with core polarization effects for the Modified Surface Delta Interaction (MSDI) and realistic Michigan three-range Yukawa (M3Y) interaction. The basic calculations included the Coulomb form factor, charge density, and the charge radii of the ground states. The Coulomb form factors for the M3Y interaction gave the best fit with the experimental data.
Keywords: Electron scattering; Coulomb form factor; Core polarization; Ground state